FORMATION OF HYDRAULIC FRACTURING CRACKS IN COMPLICATED CARBONATE RESERVOIRS WITH NATURAL FRACTURING - Dmitriy A. Martyushev; Inna N. Ponomareva; Evgeniy V. Filippov; Yuwei Li (Известия Томского политехнического университета: Инжиниринг георесурсов, 2022)
The relevance of the research is caused by the fact that the presence of natural fracturing in complex carbonates reservoirs is the main factor that affects the shape and propagation of the network of hydraulic fractures. In such cases, when a hydraulic fracture collides with natural fracturing, there may be a different nature of their interaction, for example, displacement, intersection, etc. Consequently, hydraulic fracturing in complex carbonate reservoirs, characterized by the presence of natural fracturing, can lead to the formation of not a symmetric fracture in its classical sense, but their complex network. Based on field observations (microseismic monitoring and studies of the void space of rocks), various degrees of complexity of hydraulic fractures have been established: from a simple relatively flat single fracture to a rather complex network of fractures. The main aim of the study is to assess the formation of complex networks of hydraulic fractures in naturally fractured carbonate reservoirs. Object: complex carbonate reservoir with a system of natural fractures. Methods: analysis of production, technological, hydrodynamic data and the results of microseismic monitoring in the process of hydraulic fracturing. Results. It was found that hydraulic fracturing in complex carbonate reservoirs often does not lead to the formation of a fracture in its classical sense – two wings propagating symmetrically from the wellbore, which is confirmed by the results of the analysis of the pressure build-up curves in diagnostic logarithmic coordinates. Hydraulic fractures can propagate into the formation directly from wells – targets of influence (classical representation), or through the existing network of natural fractures located in the drainage zone. To involve a significant number of natural fractures and other types of voids in the filtration process during hydraulic fracturing, it is advisable to pump the fracturing fluid at low speeds. Control over the development of hydraulic fractures should be based on reliable information about the natural fracturing of the reservoir before the event, and regulation – through monitoring the dynamics of pressure and injection rate, which confirms the research results.